2020
DOI: 10.3390/cancers12051185
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Autophagy for Renal Cell Carcinoma Therapy

Abstract: Kidney cancer is the 7th most prevalent form of cancer in the United States with the vast majority of cases being classified as renal cell carcinoma (RCC). Multiple targeted therapies have been developed to treat RCC, but efficacy and resistance remain a challenge. In recent years, the modulation of autophagy has been shown to augment the cytotoxicity of approved RCC therapeutics and overcome drug resistance. Inhibition of autophagy blocks a key nutrient recycling process that cancer cells utilize for cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 90 publications
(78 reference statements)
0
36
0
Order By: Relevance
“…It has been reported that about 33% of RCC has already metastasized at the first diagnosis, and 20% ~ 50% of patients will progress to metastasis following surgery [6,1]. Despite ccRCC treatment has developed for decades, the advanced and metastatic ccRCCs are still challenging due to its resistance to chemo-and radiotherapy, therefore RCC patients are still confronted with worse prognosis [1]. Although enormous efforts about identifying appropriate biomarkers for ccRCC tumorigenesis, progression and aggressiveness have been made to improve the efficiency of ccRCC diagnosis and prognosis, to date fewer particular biomarkers exhibit satisfactory potential for ccRCC classification and prognosis prediction or is ready for widespread use in clinical application [1,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that about 33% of RCC has already metastasized at the first diagnosis, and 20% ~ 50% of patients will progress to metastasis following surgery [6,1]. Despite ccRCC treatment has developed for decades, the advanced and metastatic ccRCCs are still challenging due to its resistance to chemo-and radiotherapy, therefore RCC patients are still confronted with worse prognosis [1]. Although enormous efforts about identifying appropriate biomarkers for ccRCC tumorigenesis, progression and aggressiveness have been made to improve the efficiency of ccRCC diagnosis and prognosis, to date fewer particular biomarkers exhibit satisfactory potential for ccRCC classification and prognosis prediction or is ready for widespread use in clinical application [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell renal cell carcinoma (ccRCC) is the most common and dangerous malignancy subtype derived from kidney tissue, accounting for approximately 80% of all renal cell carcinoma cases [1,2]. Globally, about 400,000 new diagnosed cases and 139,000 death cases are expected to occur per year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Interferon, Resveratrol, Miltefosine, Perifosine, Filipin, MCD, Emodin, monounsaturated and polyunsaturated fatty acids (MUFAs and PUFAs, respectively), diets with linoleic acid, oleic acid, marine fish oils are believed to be the perturbators of the cell membrane fluidity and are utilized for cancer treatment or prevention [ 93 ]. Chloroquine or hydroxychloroquine (HCQ) is an FDA-approved inhibitor of autophagy; ROC-325, Lys05, and DQ661 are the newest most potent inhibitors of autophagy from preclinical trials [ 94 , 95 ]. Note that HALAVEN, the actin-modifying agent, prevents glioma transitions to the mesenchymal subtype induced by the hypoxic condition.…”
Section: Potential Pharmacological Modulators Of Cell Fusionmentioning
confidence: 99%
“…It has been shown to induce potent cytotoxic effects in VHL-deficient ccRCC cells, compared to their VHL wild-type counterparts [41]. The STF-62247-stimulated synthetic lethality occurs in a HIF-independent manner through autophagy; however, the mechanistic links between VHL and autophagy are incompletely understood [42].…”
Section: Targeting Trunk Mutationsmentioning
confidence: 99%